Comparing phthalate exposure between bottlenose dolphins (Tursiops truncatus) residing in urban and rural environments - Miranda K. Dziobak; Tita Curtin; Randall S. Wells; Ryan Takeshita; Cynthia R. Smith; Eric Zolman; Christina N. Toms; Robyn F. Allen; Leslie B. Hart (Frontiers in Marine Science, 2025)
Introduction Exposure to phthalate esters has previously been documented in bottlenose dolphins ( Tursiops truncatus ) inhabiting an urban estuary (Sarasota Bay, FL, USA; 2010-2019). Phthalates are chemicals commonly added to plastic products and consumer goods to enhance qualities such as flexibility, fragrance, and stability. Chemical leaching from products into the marine environment leaves wildlife vulnerable to reproductive, developmental, and metabolic impairment. Environmental phthalate exposure has been shown to vary relative to human activity and urbanization. Methods To evaluate potential differences in dolphin exposure risk, urine was collected from free-ranging bottlenose dolphins residing in an urban (Sarasota Bay, FL, USA; 2010-2024; n=71) and rural estuary (Barataria Bay, LA, USA; 2011- 2023; n=45). Urinary phthalate metabolite concentrations were quantified with high-performance liquid chromatography (HPLC; Agilent 1100; WatersXBridge BEH C18, 2.5 μm, 2.1x50 mm analytical column) coupled to a triple quadrupole mass spectrometer (MS; Applied Biosystems Sciex API 4000) with an electrospray ionization (ESI negative) interface. Results The magnitude of MEHP detection did not differ significantly between sampling sites (p=0.97); however, MEHP was detected more frequently in Sarasota Bay dolphins (73.24%; n=52; 95% CI: 61.20-82.73) than Barataria Bay dolphins (33.33%; n=15; 95% CI: 20.00-48.95%). Dolphins from Sarasota Bay may be exposed to a greater diversity of phthalates compared to Barataria Bay dolphins, indicated by differences in the detected phthalate metabolite profile. Discussion Notably, dolphins from Barataria Bay were impacted by the Deepwater Horizon oil spill, with evidence suggesting long-term negative health outcomes. The endocrine-disrupting effects of phthalates could exacerbate metabolic, reproductive, or immune dysfunction in dolphins, especially those with compromised health. The higher phthalate detection frequency in Sarasota Bay dolphins suggests increased urban exposure risks; however, detection in dolphins from Barataria Bay raises concerns for dolphins in recovering ecosystems. Further research is needed to assess potential synergistic impacts of chemical mixtures, and targeted mitigation strategies in contaminated environments.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)